Towards Automated Playtesting in Game Development - Pereira, Nathalya Stefhany; Lima, Phyllipe; Guerra, Eduardo; Meirelles, Paulo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Digital games are also a software product. However, games have a fun requirement and tightly coupled UI, which makes them hard to test. Nevertheless, they are made of code and might also benefit from the advantages that automated tests bring to enterprise software systems. In this paper, we discuss two categories of automated tests for games, focusing on playtesting. We used the Unity Game Engine to build our tests on top of the NUnit framework and the Unity Test Framework. To demonstrate our approach for automated playtesting, we developed a 2D Arkanoid-style game. We also present the steps we took to make the testing feasible.